PEDAGOGICAL CONDITIONS FOR TRAINING MILITARY AVIATION SPECIALISTS BASED ON EXPERIENCE QUALIFIED PERSONNEL (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article reveals the pedagogical conditions for training military aviation specialists based on the experience of qualified personnel.